皮脂腺细胞通过促进辅助性T细胞17的分化从而引起皮肤炎症. (29th March 2018) - Mattii, M.; Lovászi, M.; Garzorz, N.; Atenhan, A.; Quaranta, M.; Lauffer, F.; Konstantinow, A.; Küpper, M.; Zouboulis, C.C.; Kemeny, L.; Eyerich, K.; Schmidt‐Weber, C.B.; et al.
Abstract : Linked Article: Mattii et al. Br J Dermatol 2018;178 :722–730